PEMBANDINGAN PELAKSANAAN PEKERJAAN PELAT LANTAI MENGGUNAKAN TULANGAN KROMO DENGAN TULANGAN DUA LAPIS DI TINJAU DARI ASPEK BIAYA DAN WAKTU - I Ketut Sucita; Fikri Chairutomo (Politeknik Negeri Jakarta, 2012)
In construction project, especially in building construction, slab structure work is one of the most expensive work componen t. Previously, most of slab structure work used kromo reinforcement. But, with knowledge development of earthquake and its difficulties, kromo reinforcement begin to be abandoned . One of the alternatives is replace that kromo reinforcement with two layer reinforcement. This two layer reinforcement system gives more choices for planner of construction to determine the correct reinforcement system in slab structure work to give the optimum result in term of cost and time aspects. Analysis of cost and time is done by structural analysis to obtain reinforcement kromo reinforcement. Furthermore, the calculation quantity of work that includes heavy reinforcement is installed, the number of bends, and the number of stem reinforcement. The time analysis is consist of cutting time, bending time and setting time. The unit price analysis is use time analysis data for workers salary component and SNI Standard unit price analysis for material cost component. Then, the result of cost analysis that contain of multiplication of unit price analysis and quantity for both of kromo and two layer reinforcement is being compared to determine the cost difference between kromo reinforcement and two layer reinforcement. Based on time analysis results, it is found that slab structure reinforcement working time with kromo reinforcement at 8th floor until 31st floor is 17,412 days. and 22,904 days for two layer reinforcement. Based on cost analysis results, it is found that cost of slab structure reinforcement at 8th floor until 31st floor with kromo reinforcement is Rp2.254.838.095,84 and Rp3.454.683.607,70 for two layer reinforcement. Keywords : kromo reinforcement, two layer reinforcement, time, cost ABSTRAK Pada pelaksanaan proyek konstruksi, khususnya konstruksi bangunan gedung, pekerjaan struktur pelat lantai merupakan salah satu komponen pekerjaan yang memerlukan biaya paling besar. Dahulu kebanyakan struktur pelat lantai menggunakan tulangan kromo. Namun, dengan berkembangnya pengetahuan mengenai gempa dan tingkat kesulitan pemasangan yang relatif tinggi sistem tulangan kromo mulai ditinggalkan. Salah satu alternatif yang dilakukan adalah mengganti tulangan kromo dengan tulangan dua lapis. Adanya dua sistem tulangan ini, dapat memberikan pilihan perencana konstruksi untuk menentukan sistem tulangan yang tepat dalam pekerjaan pelat lantai, sehingga mampu memberikan hasil yang optimal ditinjau dari segi biaya dan waktu. Analisis biaya dan waktu dilakukan dengan analisis struktur untuk mendapatkan tulangan kromo terpasang. Selanjutnya dilakukan perhitungan kuantitas pekerjaan yang meliputi berat tulangan terpasang, jumlah bengkokan, dan jumlah batang yang terpasang. Analisis waktu yang dilakukan meliputi waktu pemotongan, waktu pembengkokan, dan waktu pemasangan. Analisis harga satuan pekerjaan menggunakan analisis waktu untuk komponen upah tenaga kerja dan analisis harga satuan menggunakan standar SNI untuk komponen bahan. Hasil analisis terhadap waktu adalah 17 hari untuk tulangan kromo dan 23 hari untuk tulangan dua lapis. Dari aspek biaya diperoleh biaya pelaksanaan pembesian pelat lantai dengan tulangan kromo sebesar Rp 2.254.838.095,84. Sedangkan biaya pelaksanaan dengan tulangan dua lapis adalah Rp3.454.683.607,70. Kata kunci : tulangan kromo, tulangan dua lapis, waktu pelaksanaan, biaya pelaksanaan